2004
DOI: 10.1007/s00436-004-1083-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of B- and T-cell immunity in toltrazuril-treated C57BL/6 WT, �MT and nude mice experimentally infected with Neospora caninum

Abstract: Neospora caninum is a protozoan parasite predominantly known for causing abortion in cattle and neuromuscular disease in dogs. So far, no efficient metaphylactic chemotherapy has been developed. In preliminary studies, toltrazuril had been successfully used against experimental neosporosis in mice and calves. In the present study, we used immunocompetent and immunodeficient mouse strains to address the role of immunity in supporting the chemotherapy of experimental N. caninum infection. WT, microMT and athymic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Thus, when applied for a few days under these experimental conditions, toltrazuril exhibits only parasitostatic activity. In experimentally infected mice a 6-day toltrazuril treatment also had a more parasitostatic rather than a parasiticidal effect (Ammann et al 2004). A clear parasiticidal effect of toltrazuril, defined in our assay by the failure to detect NcGRA2 mRNA, was first observed after a continuous longterm treatment of 14 days.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, when applied for a few days under these experimental conditions, toltrazuril exhibits only parasitostatic activity. In experimentally infected mice a 6-day toltrazuril treatment also had a more parasitostatic rather than a parasiticidal effect (Ammann et al 2004). A clear parasiticidal effect of toltrazuril, defined in our assay by the failure to detect NcGRA2 mRNA, was first observed after a continuous longterm treatment of 14 days.…”
Section: Discussionmentioning
confidence: 65%
“…In the murine model of experimental N. caninum infection, toltrazuril treatment prevented severe clinical signs and the formation of cerebral lesions (Gottstein et al 2001 ;Darius et al 2004 a). However, Ammann et al (2004) clearly demonstrated that an efficient metaphylaxis requires at least a T-cell-mediated immunological support in mice. We now used NcGra2 as a target gene to demonstrate viability or non-viability of N. caninum in affected host cells following treatment with the anti-parasitic compound toltrazuril.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the outcome of infection, both one and three toltrazuril applications significantly delayed the outbreak of congenitally acquired neosporosis in newborn mice, as pups treated once or three times with toltrazuril diseased at a significantly later time point when compared to placebotreated pups. A marked delay of disease after toltrazuril treatment had already been observed in N. caninuminfected athymic nu − /nu − mice (Ammann et al 2004), and these experiments had indicated that toltrazuril had a parasitostatic rather than a parasiticidal effect, requiring T cell-mediated support to control neosporosis. In the present study, the overall proportion of surviving animals in the three-time-toltrazuril-treated group was 1.6 times higher than the proportion of one-time-treated pups.…”
Section: Discussionmentioning
confidence: 85%
“…In the murine model of experimental N. caninum infection, toltrazuril treatment prevented severe clinical signs and formation of cerebral lesions (Gottstein et al 2001;Darius et al 2004a, b). However, an efficient metaphylaxis required at least a T cell-mediated immunological support in mice (Ammann et al 2004). It was also reported that toltrazuril treatment of an acute N. caninum infection-induced during pregnancy in miceresulted in a significant reduction of fetal losses (Gottstein et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…during pregnancy in cattle or dogs, may putatively prevent the diaplacental passage of the parasite or may considerably reduce the abortion risk during conatal neosporosis. Explorative investigations had shown that toltrazuril, a triazinone derivative, can be effective against experimental neosporosis in the murine (Eperon et al 1999, Gottstein et al 2001 and bovine (Kritzner et al 2002) model, and that an efficient metaphylaxis requires at least a T-cell-mediated immunological support (Ammann et al 2004). This may be explained by a parasitostatic rather than a parasitocidal effect of the compound.…”
Section: Experimental Parasite Cell Affection By Chemotherapymentioning
confidence: 99%